2000
DOI: 10.4141/p99-020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tillage type on vertical weed seedbank distribution in a sandy soil

Abstract: Influence of tillage type on vertical weed seedbank distribution in a sandy soil. Can. J. Plant Sci. 80: [455][456][457]. The vertical distribution of weed seeds in the seedbank of a sandy soil under three tillage systems (moldboard plow, chisel plow, and no-till) was estimated by a seedling-emergence method. The vertical distribution of the weed seedbank differed with tillage type and depth of tillage. The no-till system had the largest portion (90%) of the seedbank in the 0-to 5-cm layer. Chisel plowing dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 10 publications
(4 reference statements)
4
68
1
1
Order By: Relevance
“…Cardina et al (1991) showed that the distribution patterns after various tillage operations for two silt loam soils were nearly identical but differed from those within a silty clay loam soil. In addition, Swanton et al (2000) observed that tillage distribution is different in sandy soil versus finer texture soils. Whether these differences were due to soil type or other management factors (e.g., autumn tillage for silt loam versus spring tillage for silty clay loam or soil water content differences) remain unknown.…”
Section: Discussionmentioning
confidence: 94%
“…Cardina et al (1991) showed that the distribution patterns after various tillage operations for two silt loam soils were nearly identical but differed from those within a silty clay loam soil. In addition, Swanton et al (2000) observed that tillage distribution is different in sandy soil versus finer texture soils. Whether these differences were due to soil type or other management factors (e.g., autumn tillage for silt loam versus spring tillage for silty clay loam or soil water content differences) remain unknown.…”
Section: Discussionmentioning
confidence: 94%
“…However, there was no significant differences in the soil seed bank between the upper and deeper soil layers in the farmland (with severe disturbance) due to its frequent and deep ploughing [43], which indicated that the severe disturbance totally changed the vertical distribution of the soil seed bank besides its composition.…”
Section: Effects Of Disturbance On Soil Seed Bank and Vegetationmentioning
confidence: 99%
“…In conventional puddled transplanting systems, existing weeds are controlled by burying weed seeds into the saturated and submerged soil that results in less early emergence of weeds [10,11]. By contrast, to achieve a similar low weed competition at crop establishment, preplanting non-selective herbicides must be used to kill the existing weeds on the non-puddled field and subsequently pre-emergence herbicide also need to apply because of remaining viable weed seeds on the surface of the non-puddled soil still after pre-plant herbicide application [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%